1996
DOI: 10.1074/jbc.271.11.6273
|View full text |Cite
|
Sign up to set email alerts
|

Nuclear Factor I as a Potential Regulator during Postembryonic Organ Development

Abstract: Nuclear factor I (NFI) family members are transcription factors that are believed to also participate in DNA replication. We have cloned two Xenopus laevis NFIs that are up-regulated by thyroid hormone. They are 84 -95% identical to their counterparts in birds and mammals. In contrast, the two Xenopus NFIs are much less homologous to each other, sharing only 58% homology, which largely resides in the DNA binding domain at the amino terminus. However, both NFIs can bind to a consensus NFI binding site and activ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

1997
1997
2020
2020

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 43 publications
(16 citation statements)
references
References 48 publications
0
16
0
Order By: Relevance
“…TR and RXR genes are highly activated during late embryogenesis, shortly after tadpole hatching (stages 35 to 36 [48 h]) but well before the synthesis of endogenous T 3 (37). This up-regulation of TR and RXR genes coincides with the down-regulation of several genes, such as the HH (64), ST3 (47), and NF-I genes (51), that are known to be expressed during both metamorphosis and embryogenesis. These genes have also been shown to be up-regulated by T 3 directly at the transcriptional level.…”
Section: Discussionmentioning
confidence: 79%
“…TR and RXR genes are highly activated during late embryogenesis, shortly after tadpole hatching (stages 35 to 36 [48 h]) but well before the synthesis of endogenous T 3 (37). This up-regulation of TR and RXR genes coincides with the down-regulation of several genes, such as the HH (64), ST3 (47), and NF-I genes (51), that are known to be expressed during both metamorphosis and embryogenesis. These genes have also been shown to be up-regulated by T 3 directly at the transcriptional level.…”
Section: Discussionmentioning
confidence: 79%
“…Early studies showed that NFI proteins are essential for adenovirus DNA replication both in vitro (1)(2)(3)(4) and in vivo (5,6) and suggested that NFI may function in cellular DNA replication. More recently, expression of the four NFI genes has been shown to be developmentally regulated (7)(8)(9), and NFI proteins have been implicated in the regulation of transcription of genes expressed in many tissues, including liver (10,11), mammary gland (12,13), and brain (14)(15)(16). To assess the role of individual NFI family members in cell growth and development, we have begun a genetic analysis of NFI function in mice.…”
mentioning
confidence: 99%
“…DNA competitors were used at a 100-fold molar excess relative to the DNA probe concentration. Antisera that recognize native NFI proteins (16) or pre-immune rabbit serum were used for supershift assays. Specific mammalian isoforms recognized by the NFI antiserum have not been determined.…”
Section: Methodsmentioning
confidence: 99%